The effect of “senam ceria” on the development of self-identity in children aged 5–6 years in group B at PAUD KB Nagaya - Sittun, Nur; Purwanto, Didik; Fitriana; Agusniatih, Andi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: The development of self-identity in early childhood is a crucial aspect that forms the foundation for self-confidence, independence, and social competence. Children with a well-developed self-identity tend to recognize themselves, understand their roles, and demonstrate positive behaviors in everyday interactions. Objective: This study aims to analyze the effect of Senam Ceria (Joyful Exercise) on the development of self-identity among children aged 5–6 years. Method: The study employed a one-group pretest–posttest design involving 18 children from Group B as research participants. The observation instrument used in this study was validated by experts and demonstrated high reliability, with a Cronbach’s Alpha coefficient of 0.87. Over a three-week period, the children participated in six sessions of Senam Ceria, which were designed to stimulate self-expression, cooperation, and social awareness. Result: The analysis revealed a significant improvement in self-identity scores, increasing from a mean score of 7.61 before the intervention to 8.94 after the intervention. The paired t-test results indicated that the calculated t-value (4.761) exceeded the critical t-value (1.73961), with a p-value of 0.000 < 0.05, indicating that Senam Ceria had a statistically significant effect on children’s self-identity development. The novelty of this study lies in its focus on Senam Ceria, which has traditionally been used to enhance motor skills, but in this research is utilized as a medium for stimulating self-identity. These findings confirm that creative physical activities not only promote physical health but also effectively foster self-awareness, responsibility, and social behavior in children. Conclusion: In conclusion, this study provides an important contribution to early childhood education by demonstrating that Senam Ceria can be integrated as a learning strategy that supports the holistic development of children’s self-identity.